THE USE OF CHLORHEXIDINE MOUTHWORKS CAN REDUCE THE ACCUMULATION OF DENTAL PLAK IN USERS OF FIXED ORTHODONTIC DEVICES: PEMAKAIAN OBAT KUMUR KLORHEKSIDIN DAPAT MENURUNKAN AKUMULASI PLAK GIGI PADA PENGGUNA PIRANTI ORTODONTI CEKAT - Dwis Syahrul; Surwandi Walianto; Priscilla Sonia Suwongto (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: Treatment of malocclusion with fixed devices is common for us to encounter everyday. In using this device there are parts that are glued to the teeth and cannot be disassembled by the patient himself. This allows food debris and plaque to adhere more easily to the teeth and the fixed appliance. Review: Dental plaque is a transparent thin layer that adheres tightly to the teeth, which contains bacteria and their products in the form of organic and inorganic materials, oral fluids, loose epithelial cells and blood cells. Plaque is influenced, among other things, by bacteria, buffers and salivary flow, the presence of fluoride and the frequency of carbohydrates consumed, crowding of teeth, rough surfaces, areas that are difficult to clean, position of teeth outside the area of occlusion, and multiplication of bacteria. Therefore, during the process of fixed orthodontic treatment, it is necessary to control plaque which is carried out mechanically or chemically. Mechanical plaque control can be done by brushing teeth and using dental floss, while chemical plaque control can be done by using mouthwash. The mouthwash that has proven to be the most effective of the other therapeutic plaque control agents is chlorhexidine because it is able to ionically adhere to teeth and oral mucosal surfaces in high concentrations for hours. Chlorhexidine 0.2% can affect the number of salivary bacterial colonies due to the phenol content contained therein. Chlorhexidine itself has a very strong binding ability in the oral cavity, which is its advantage compared to other ingredients. Conclusion: Gargling with chlorhexidine can reduce plaque accumulation and improve oral hygiene status in fixed orthodontic users